STUDI KOMPARATIF TENTANG KEBIASAAN BELAJAR SISWA KELAS XI IPS DENGAN SISWAKELAS XI IPA SMA MUHAMMADIYAH 1 PEKANBARU TP 2013/2014 - Adrianto '; Elni Yakub Elni Yakub; Zulfan Saam Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :This thesis is an descriptive comparative with population student of class XI IPS and IPA SMA Muhammadiyah 1 Pekanbaru. The methode for sampling is total sampling that 218 students. Instrument for this research is questioner, then distribute to all students of class XI. Than data calculating with statistic. Hipotesis that proposed is study habits student of class  XI IPS same with study habits students of class XI IPA. According to research result which is conducted that  with mean . So can be known that there is no different about study habits student of XI IPS with student of XI IPA. So can be concluded that study habits student of class XI IPS is same with study habits student of class XI IPA SMA Muhammadiyah 1 Pekanbaru.   Keyword :Study Habits IPA IPS